2011
DOI: 10.4028/www.scientific.net/amm.80-81.870
|View full text |Cite
|
Sign up to set email alerts
|

The Application Study of Accumulator Used in Hydraulic System of 20MN Fast Forging Machine

Abstract: Based on the description of 20MN fast forging press hydraulic system, the paper analyzed the possibility of energy conservation which the accumulator made in the fast forging machine system. When accumulator was used in fast forging machine, then analyzed the calculation results, and the energy conservation program of fast forging machine energy accumulator was evaluated briefly. The test system was set up on 20MN fast forging machine, and the paper researched the application of accumulator in fast forging pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The results showed that the compound system increased the energy efficiency by approximately 39%. Dai et al [29] applied a recovery accumulator to a 16 MN fast forging hydraulic press to reduce the installed power by the absorption of large flow and pressure pulses. Results show that the accumulator has promising energy-saving effects.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the compound system increased the energy efficiency by approximately 39%. Dai et al [29] applied a recovery accumulator to a 16 MN fast forging hydraulic press to reduce the installed power by the absorption of large flow and pressure pulses. Results show that the accumulator has promising energy-saving effects.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on the energy efficiency of hydraulic presses have mainly concentrated on energy matching and energy recovery. When it comes to energy recovery, an energy regeneration system is used to recover and store in an accumulator the kinetic energy or gravity potential energy of the hydraulic press slider that will be released during the subsequent operation [16][17][18][19][20]. To match the loads and improve efficiency, the operational parameters of the hydraulic press are examined and improved using data envelopment theory [21].…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [18] proposed a flywheel energy-saving system (FESS) that can store the redundant energy at no-load stages and low-load stages and then release the stored energy at high-load stages. Dai et al [19] applied a hydraulic accumulator to a 20 MN fast forging hydraulic press to realize energy conversion by absorbing large flow-pressure pulses and hydraulic shock. The results show that the hydraulic accumulator has promising energy-saving effects.…”
Section: Introductionmentioning
confidence: 99%